2007
DOI: 10.1088/0951-7715/20/11/006
|View full text |Cite
|
Sign up to set email alerts
|

Metastability in interacting nonlinear stochastic differential equations: I. From weak coupling to synchronization

Abstract: We consider the dynamics of a periodic chain of N coupled overdamped particles under the influence of noise. Each particle is subjected to a bistable local potential, to a linear coupling with its nearest neighbours, and to an independent source of white noise. The system shows a metastable behaviour, which is characterised by the location and stability of its equilibrium points. We show that as the coupling strength increases, the number of equilibrium points decreases from 3 N to 3. While for weak coupling, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 37 publications
1
68
0
Order By: Relevance
“…For small γ, H( γ) grows like the square-root of γ. This is compatible with the weakcoupling behaviour H = (1/4 + 3/2γ + O(γ 2 ))/N obtained in [BFG06a], if one takes into account the scaling of γ.…”
Section: Stochastic Casesupporting
confidence: 89%
See 4 more Smart Citations
“…For small γ, H( γ) grows like the square-root of γ. This is compatible with the weakcoupling behaviour H = (1/4 + 3/2γ + O(γ 2 ))/N obtained in [BFG06a], if one takes into account the scaling of γ.…”
Section: Stochastic Casesupporting
confidence: 89%
“…In the previous paper [BFG06a], we showed that the number of stationary configurations increases from 3 to 3 N as the coupling intensity γ decreases from a critical value γ 1 of order N 2 to 0. This transition from strong to weak coupling involves a sequence of successive symmetry-breaking bifurcations, and we analysed in particular the first of these bifurcations, which corresponds to desynchronisation.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations